The effect of foot reflexology on constipation and quality of life in patients with multiple sclerosis. A randomized controlled trial. (January 2020) - Sajadi, Mahbobeh; Davodabady, Fahimeh; Naseri-Salahshour, Vahid; Harorani, Mehdi; Ebrahimi-monfared, Mohsen
Highlights: Complementary and alternative medicine are more popular and accessible in Iran. Foot reflexology significantly improve the constipation in patients with MS. Reflexology can be used as a safe, non-invasive and easy nursing intervention to management of the complications in MS. Abstract: Background: Constipation is a major problem in most patients with multiple sclerosis (MS). The aim of this study was to investigate the effect of foot reflexology on constipation and quality of life in patients with MS. Methods: This study was a randomized controlled trial, in which 63 patients with MS referred to Arak MS Society, Iran were participated (from May to Dec. 2018). In this study participants were selected according to inclusion criteria and randomly divided into intervention (n = 33) and control (n = 30) groups. In the intervention group, foot reflexology was applied twice a week for 6 weeks (each session lasted about 30−40 min). Data were collected using demographic questionnaire, Constipation Assessment Scale (CAS) and Short Form (SF) 36 Quality of Life (QOL) questionnaire. Finally, the data were analyzed using SPSS Ver. 16 and descriptive and inferential statistical tests. Results: The results of the study showed that severity of constipation and QOL score were not significant between the two groups before intervention (p > 0.05), but; after intervention, severity of constipation significantly decreased in the reflexology group (p < 0.05). Nevertheless, after intervention, the QOL was improved in the reflexology group compared to the control group but was not significant (p > 0.05). Conclusion: The results of this study showed that foot reflexology, as an effective intervention can be useful in management of constipation in patients with MS. Therefore, this intervention can be applied as a safe method for the decrease of constipation in MS patients.